Group Guidance Using Reality Approach to Overcome Smoking Behavior of Junior High School Students - Intan Verly Syafitri; Zadrian Ardi; Netrawati Natrawati (Jurnal Counseling Care, 2024)
Smoking is a serious health problem, especially for teenagers. Smoking behavior in junior high school students needs to receive appropriate attention and treatment. One approach that can be used to overcome smoking behavior in junior high school students is group guidance using a reality approach. The reality approach in group guidance helps students to understand their own reality and the consequences of smoking behavior. Through this approach, students are helped to develop responsibility for their own behavior and make healthier choices. Keywords: Group Guidance, Reality Approach, Smoking Behavior